Polysaccharide-based hydrogels crosslink density equation: A rheological and LF-NMR study of polymer-polymer interactions. (1st February 2022) - Kopač, Tilen; Abrami, Michela; Grassi, Mario; Ručigaj, Aleš; Krajnc, Matjaž
Abstract: A simple relation between pendant groups of polymers in hydrogels is introduced to determine the crosslink density of (complex) hydrogel systems (mixtures of 2, 2, 6, 6-tetramethylpiperidine-1-oxyl (TEMPO) modified nanocellulose, alginate, scleroglucan and Laponite in addition of crosslinking agents). Furthermore, the rheological properties and their great potential connection to design complex hydrogel systems with desired properties have been thoroughly investigated. Hydrogel structures governing internal friction and flow resistance were described by the predominant effect of ionic, hydrogen, and electrostatic interactions. The relationship between rheological properties and polymer-polymer interactions in the hydrogel network is explained and expressed in a new mathematical model for determining the crosslink density of (crosslinked) hydrogels based on single or mixture of polymer systems. In the end, the combined used of rheology and low field nuclear magnetic resonance spectroscopy (LF-NMR) for the characterization of hydrogel networks is developed. Graphical abstract: Unlabelled Image